The First Korean case of combined oxidative phosphorylation deficiency-17 diagnosed by clinical and molecular investigation - Young A Kim; Yoo-Mi Kim; Yun-Jin Lee; Chong Kun Cheon (Korean Pediatric Society, 2017)
Combined oxidative phosphorylation deficiency-17 (COXPD-17) is very rare and is caused by homozygous or compound heterozygous mutations in the ELAC2 gene on chromosome 17p12. The ELAC2 gene functions as a mitochondrial tRNA processing gene, and only 4 different pathogenic mutations have been reported in ELAC2-associated mitochondrial dysfunction involving oxidative phosphorylation. Affected patients show various clinical symptoms and prognosis, depending on the genotype. We report a novel mutation in the ELAC2 gene (c.95C>G [p.Pro32Arg], het), in an infant with COXPD-17 who presented with encephalopathy including central apnea and intractable epilepsy, and growth and developmental retardation. During hospitalization, consistently elevated serum lactic acid levels were noted, indicative of mitochondrial dysfunction. The patient suddenly died of shock of unknown cause at 5 months of age. This is the first case report of COXPD-17 in Korea and was diagnosed based on clinical characteristics and genetic analysis.